2023
DOI: 10.1186/s13287-023-03300-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered tissue and cell therapy products are efficiently cryopreserved with pathogen-inactivated human platelet lysate-based solutions

Abstract: Background There remains much interest in improving cryopreservation techniques for advanced therapy medicinal products (ATMPs). Recently, human platelet lysate (hPL) has emerged as a promising candidate to replace fetal bovine serum (FBS) as a xeno-free culture supplement for the expansion of human cell therapy products. Whether hPL can also substitute for FBS in cryopreservation procedures remains poorly studied. Here, we evaluated several cryoprotective formulations based on a proprietary hP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
2
1
0
Order By: Relevance
“…Previous reports have compared canine mesenchymal stem cells stored in cryopreservation solution for approximately 1 year with those stored unfrozen and showed comparable survival rates, cell markers, and functionality [11]. In humans, the viability and functionality of platelets frozen in sheet form for 18 months do not differ from those of non-frozen platelets [12]. These results are consistent with our results, indicating that the cells retain viability, functionality, and differentiation capacity after cryopreservation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous reports have compared canine mesenchymal stem cells stored in cryopreservation solution for approximately 1 year with those stored unfrozen and showed comparable survival rates, cell markers, and functionality [11]. In humans, the viability and functionality of platelets frozen in sheet form for 18 months do not differ from those of non-frozen platelets [12]. These results are consistent with our results, indicating that the cells retain viability, functionality, and differentiation capacity after cryopreservation.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we confirmed that porcine MNs can be preserved for 2 years using proper storage procedures. Cell cryopreservation studies have shown that canine and human adipose tissues, platelets, pancreatic cells [8][9][10][11][12], and even small organs, such as rat kidneys, can be cryopreserved [13]. Although intracellular ice crystal formation presents a challenge in the cryopreservation process, it can be averted by adequate immersion in a suitable freezing solution and replacement of water content.…”
Section: Discussionmentioning
confidence: 99%
“…There are different protocols and studies on cryopreservation based both on xeno-free commercial solutions and on human platelet lysate in different cell types, mainly in MSCs from the umbilical cord, bone marrow, and adipose tissue. These have shown that DMSO combined with PL in different concentrations maintains cell viability and proliferation after post-thawing recovery and that PL can function as a substitute for FBS in cryopreservation solutions [42][43][44][45], a conclusion similar to that which can be inferred from the results of this study.…”
Section: Discussionsupporting
confidence: 85%